Benthic foraminifera as indicators of natural variability and anthropogenic impact - Dijkstra, Noortje (Universitetet i Tromsø, 2013)
The papers of this thesis are not available in Munin: 1. Dijkstra, N., Junttila, J., Carroll, J., Husum, K., and Hald, M.: 'The impact of contaminants and grain size on benthic foraminiferal assemblages in the harbor of Hammerfest, northern Norway', (manuscript) 2. Dijkstra, N., Junttila, J., Carroll, J., Husum, K., Elvebakk, G., Godtliebsen, F., and Hald, M.: 'Baseline benthic foraminiferal assemblages and habitat conditions in a sub-Arctic region of increasing petroleum development', Marine Environmental Research (2013), vol. 92:178–196. Available at http://dx.doi.org/10.1016/j.marenvres.2013.09.014 3. Dijkstra, N., Junttila, J., Husum, K., Carroll, J., and Hald, M.: 'Natural variability of benthic foraminiferal assemblages and metal concentrations during the last 150 yrs. in the Ingøydjupet trough, SW Barents Sea', (manuscript) 4. Junttila, J., Carroll, J., Husum, K., and Dijkstra, N.: 'Sediment transport and deposition in the Ingøydjupet trough, SW Barents Sea', (manuscript) 5. Schönfeld, J., Alve, E., Geslin, E., Jorissen, F., Korsun, S., Spezzaferri, S., and Members of the FOBIMO group: 'The FOBIMO (Foraminiferal Bio-Monitoring) initiative – Towards a standardized protocol for soft-bottom benthic foraminiferal monitoring studies', Marine Micropaleontology (2012), vol. 94-95:1-13. Available at http://dx.doi.org/10.1016/j.marmicro.2012.06.001 Benthic foraminifera (micro-organism living on the sea-floor) were studied in the southwestern Barents Sea and Hammerfest harbor. The study focused on the response of the micro-organisms to natural and man made environmental changes. The study shows that the southwestern Barents sea is relatively clean, and the foraminifera are only impacted by natural changes. However, in the Hammerfest harbor, pollution had severe impact on the organisms. Understanding the response of the foraminifera to different types of environmental changes can be used to develop a bio-monitoring tool. Such a bio-monitoring tool based on foraminifera helps to register environment deterioration ...